Clostridium perfringens Bacteraemia following Normal Vaginal Delivery - Mokhamad Zhaffal; Anastasia Salame; Johnny Awwad (Case Reports in Infectious Diseases)
Clostridial uterine infections and bacteraemia are of a rare occurrence, especially in the absence of risk factors. However, when encountered, they can carry significant morbidity and mortality rates. We present a rare case of C. perfringens bacteraemia in the immediate postpartum period of a noncomplicated vaginal delivery. Prompt diagnosis and early initiation of treatment were imperative for ensuring a safe recovery of the patient. Despite the fact that bacteraemia caused by C. perfringens is an infrequent event in the uneventful postpartum phase, maintaining vigilance for the potential occurrence of such an event allows for early detection and timely administration of antibiotics and resuscitative measures.